Development of posture and gait across the life span - Shumway-Cook, Anne 1947-; Woollacott, Marjorie H. 1946-
Representing the latest in theory, research, and practice, this book looks at posture and gait control from both a behavioral and a neurophysiological perspective as it develops and declines across a life span. It covers the role of neural systems, the importance of physical activity, and abnormalities. Sections include developmental theories and their relation to posture and gait; the development of balance and locomotion of children; posture and gait changes associated with aging; and posture and gait in exceptional populations. This is a topic that is rapidly becoming a primary focus for experimental and clinical research